Methodical aspects of risk insurance companies - Maksym Zhytar (Cхід, 2016)
The article presents a diagram of the main risk groups and highlights their causes. It is stated that the insurance companies manage risk it is advisable to allocate 4 groups of assessment methods that are most suitable and practical in the real sphere: expert, economic-statistical, computational and analytical, analog. Justified and effective methods of risk control considered. Conclusions regarding the following methods and techniques of risk management of insurance companies, which contain a number of different measures of organizational and financial nature and allow a certain extent, anticipate the consequences and the extent of damage to be reimbursed. The primary role in the management of insurance risks should be provided methods of risk financing, aimed at generating sufficient in terms of the sources of their coverage. This effect can provide underwriting system and a set of measures of risk management Risk management adopted by the insurance. In addition, the importance of risk management in the domestic practice, noted as one of the most promising directions of development of the domestic insurance market.